2020
DOI: 10.1007/s00204-020-02747-w
|View full text |Cite
|
Sign up to set email alerts
|

The chemical convulsant diisopropylfluorophosphate (DFP) causes persistent neuropathology in adult male rats independent of seizure activity

Abstract: Organophosphate (OP) threat agents can trigger seizures that progress to status epilepticus, resulting in persistent neuropathology and cognitive deficits in humans and preclinical models. However, it remains unclear whether patients who do not show overt seizure behavior develop neurological consequences. Therefore, this study compared two subpopulations of rats with a low versus high seizure response to diisopropylfluorophosphate (DFP) to evaluate whether acute OP intoxication causes persistent neuropatholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 44 publications
8
21
0
Order By: Relevance
“…However, a time‐course examination of temporal, morphological, and memory function changes is beyond the scope of this study, which is intended to capture the long‐term impact of NA exposure. There are a few previous studies on the temporospatial progression of neuroinflammation in a rat model of DFP intoxication 56–58 . These reports are consistent with our results on the persistent, long‐term neuropathological dysfunction in the soman model.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, a time‐course examination of temporal, morphological, and memory function changes is beyond the scope of this study, which is intended to capture the long‐term impact of NA exposure. There are a few previous studies on the temporospatial progression of neuroinflammation in a rat model of DFP intoxication 56–58 . These reports are consistent with our results on the persistent, long‐term neuropathological dysfunction in the soman model.…”
Section: Discussionsupporting
confidence: 92%
“…There are a few previous studies on the temporospatial progression of neuroinflammation in a rat model of DFP intoxication. [56][57][58] These reports are consistent with our results on the persistent, long-term neuropathological dysfunction in the soman model. However, potential differences in temporal aspects of neuroinflammation were also observed, such as its persistence for 3 months postexposure to soman.…”
Section: Long-term Brain Structural Changessupporting
confidence: 92%
See 1 more Smart Citation
“…Overall, the present results are consistent with previous studies of OP-induced SE, in which it was concluded that neurodegeneration and neuroinflammation are mediated by independent mechanisms, 92 and that seizure severity and duration are not the only variables driving neuronal cell loss. 90 In conclusion, our results confirm that MDZ at a dose equivalent to that recommended for the treatment of OP nerve agent seizures does not terminate DFP-induced SE in a rat model when administered 40 min after seizure onset. However, when ALLO or ALLO + PPL are administered with the same dose of MDZ, SE is generally terminated and there is reduced neurodegeneration.…”
Section: Discussionsupporting
confidence: 75%
“…Intermittent seizures and brief seizure relapse were observed in the 3-day period after treatment with the three-drug combination, likely due to the persistence of brain cholinesterase inhibition. 89,90 We do not consider the occurrence of such early spontaneous seizures to be an indication of epileptogenesis. However, the animals in the MDZ-only group exhibited spontaneous seizures that persisted for up to 7.5 months and clearly had become epileptic.…”
Section: Discussionmentioning
confidence: 99%